ChemInform Abstract: Silver‐Catalyzed Cyclization of N‐(Prop‐2‐yn‐1‐yl)pyridin‐2‐amines. Issue 20 (25th April 2013) - Chioua, Mourad; Soriano, Elena; Infantes, Lourdes; Jimeno, M. Luisa; Marco‐Contelles, Jose; Samadi, Abdelouahid
Abstract This reaction yields 3‐methyl‐imidazo[1, 2‐α]pyridines (II) from readily available substrates.